The Effectiveness of SOLE on EFL Learning for Vocational Students in Indonesia - Armyta Puspitasari; Nurul Fitria Aprilliani; Arinda Lelian; Sapto Priyanto (UIR Press, 2023)
Improving education in the 4.0 era needs to be adjusted to the teaching and learning in higher education. Thus, it is necessary to have a learning strategy that prioritizes student independence in learning by using facilities in the digital era such as the internet. Therefore, SOLE can be one of the strategies that are in accordance with this 4.0 education. The purpose of this study was to find out the effectiveness of SOLE for apprentices in English as a Foreign Language (EFL) classrooms. In this study, we used quasi-experimental studies conducted through pre-test and post-test on study subjects as primary data for the study. The analysis showed a significant difference between students taught using SOLE and conventional methods in English proficiency. The Wilcoxon test results prove that the two-sided asymptotic significance of the Wilcoxon test is 0.000 for experimental class, and 0.000 for control class which the Asymptotic significance 2-tailed below Alpha (0.05). It means that SOLE can be more effective than lecturing.